Catalisadores de CuO/CeO2 promovidos com Au e Pt - estudo do impacto da interface e das propriedades eletrônicas do Cu no desempenho catalítico na reação de CO-PROX - Cruz, Aline Rodrigues Miranda (2020)
The copper-ceria system has been extensively investigated to be used as a catalyst in the preferential oxidation of CO reaction (CO-PROX), aiming the purification of H2 streams from reformed fuels, due to its oxygen storage capacity and redox properties. However, many aspects of these catalysts must be better understood, such as the impact of successive redox cycles on the copper-ceria interaction, the role played by copper species in the CO-PROX reaction mechanism and the effect of adding noble metals to CuO/CeO2 catalysts in the properties and performance in the reaction. These issues were addressed in this thesis. CuO/CeO2 catalysts with 1 to 3% of copper promoted or not with Au and Pt were synthesized by different methods, characterized by physical-chemical techniques, and applied in the PROX reaction. The results showed that the stability of the CuO/CeO2 interface, submitted to successive redox cycles, is important to the CO-PROX reaction and that this stability depends on the employed synthesis method. For co-precipitated materials, it was verified that the CO-PROX reaction is impacted by the nature of the Cu species, which may vary with the reaction temperature, depending on the amount of metal in the material. From these results, it was proposed a new PROX reaction mechanism for these materials. In addition, our results indicated that the materials synthesized by impregnation and co-precipitation follow different preferential pathways in the PROX reaction. After understanding these aspects, the effect of adding Au and Pt to Cu/ceria catalysts was evaluated. The increase in gold content from 0% to 0.75% worsened the performance in the CO-PROX reaction, which may be associated with the gold particle size, higher than 10 nm, and the possible blocking of Cu sites by deposition of Au, resulting in less interaction between Au-Cu-Ce. The promotion of the CuO/CeO2 catalyst with platinum also did not bring benefits in the ideal CO-PROX reaction, which can be explained by the stability of the Pt0-CO bond up to 120 ºC during the reaction. On the other hand, with the addition of CO2 and water in the reaction stream, i.e. under real CO-PROX conditions, the PtCu bimetallic material showed a promising result up to 120 ºC, with greater resistance to the presence of these reactants. Therefore, this thesis provides a new perspective on the redox property, on the CO-PROX reaction mechanism and on the addition of noble metals on CuO/CeO2 catalysts, based on consistent results of in situ and ex situ characterizations.